Solubility and Dissolution Enhancement of Poorly Soluble Drug Aripiprazole through Solid Dispersion - Y Anand Kumar; Srivatsa Sangawar (Asian Journal of Pharmaceutical Research and Development, 2024)
Aripiprazole (ARP) having lowest water solubility indicates class II drugs of BCS. These classes of drugs could potentially exhibit dissolution rate limited absorption. The objective of the present study is to improve the solubility and dissolution of Aripiprazole through solid dispersion (SD) technique. ARP-SDs were prepared by Kneading (KNE), Solvent evaporation (SE), Melt solvent (MS) and Microwave irradiation (MW) methods using PEG 4000, PEG 6000 at 1:1, 1:4 ratios. ARP-SDs were studied in solution state by solubility, in vitro dissolution rate and solid state by FTIR, XRD, and relative dissolution parameters through PCP Disso V3 software. The FTIR studies indicate no interaction in all the ARP-SDs, the powder XRD studies indicate lot of decrement in the principle peak heights of ARP in ARP-SDs suggest the transformation of crystalline ARP into nearer amorphous state predicting micronization mechanism. The solubility was improved linearly with increase in concentrations PEG 4000 and PEG 6000. The amount of ARP release from ARP-SDs prepared by KNE were found to be greater than other ARP-SDs and was in the order KNE>SE>MS >MW >PM>ARP. The dissolution of ARP-SDS, obeyed first order kinetics and model fitted with Hixon crowel. One-way ANOVA results suggest the DP60, and DE60 values were significantly higher (P<0.01) in ARP-SDS than pure drug. The result concludes that solid dispersion technique was can be used increase the solubility and dissolution of poorly soluble drug Aripiprazole.